Some Thoughts on Procedure and Evidence before the EU Courts in Competition Cases and Restrictive Measures relating to Ukraine - Valančius, Virgilijus (Teisė, 2024)
During the last twenty years, both jurisdictions of the European Union Court of Justice have laid down many general principles in competition matters as well as, to a lesser extent, in restrictive measures litigation, relating to essential issues concerning evidence and procedure.In competition matters, it arises from the judicial control of the European Commission decisions regarding both infringements of the competition rules applicable to undertakings and fines of a non-criminal nature sanctioning undertakings,– that burden of proof lies with the European Commission; however, the principal issue remains the one of the unfettered evaluations of evidence. It is only the reliability of the evidence before the EU courts which is decisive when it comes to its evaluation. At the same time, undertakings may rely on principles of pure administrative nature, e.g., duty to state reasons, but also of a more criminal nature, e.g., the rights of the defence.Restrictive measures, which are neither of a criminal nature, i.e. freezing of funds and restrictions on entry into the territory of the Member States, adopted by the Council under the European Common foreign and security policy (CFSP) raised very similar issues at EU Courts, who hear relevant cases.On the basis of the analysis of the case law of the EU Courts, the article addresses the question whether some approaches and solutions in competition law cases should be transposed into restrictive measures litigation, especially in the context of the war in Ukraine.
Keywords: Court of Justice; General Court; procedure; competition cases; fines; Common Foreign and Security Policy (CFSP); restrictive measures; restrictive measures adopted in view of the situation in Ukraine